Current research priorities in chronic fatigue syndrome/myalgic encephalomyelitis: disease mechanisms, a diagnostic test and specific treatments. Issue 2 (25th August 2006) - Kerr, J R; Christian, P; Hodgetts, A; Langford, P R; Devanur, L D; Petty, R; Burke, B; Sinclair, L I; Richards, S C M; Montgomery, J; McDermott, C R; Harrison, T J; et al.
Abstract : Chronic fatigue syndrome (CFS) is an illness characterised by disabling fatigue of at least 6 months duration, which is accompanied by various rheumatological, infectious and neuropsychiatric symptoms. A collaborative study group has been formed to deal with the current areas for development in CFS research—namely, to develop an understanding of the molecular pathogenesis of CFS, to develop a diagnostic test and to develop specific and curative treatments. Various groups have studied the gene expression in peripheral blood of patients with CFS, and from those studies that have been confirmed using polymerase chain reaction (PCR), clearly, the most predominant functional theme is that of immunity and defence. However, we do not yet know the precise gene signature and metabolic pathways involved. Currently, this is being dealt with using a microarray representing 47 000 human genes and variants, massive parallel signature sequencing and real-time PCR. It will be important to ensure that once a gene signature has been identified, it is specific to CFS and does not occur in other diseases and infections. A diagnostic test is being developed using surface-enhanced, laser-desorption and ionisation-time-of-flight mass spectrometry based on a pilot study in which putative biomarkers were identified. Finally, clinical trials are being planned; novel treatments that we believe are important to trial in patients with CFS are interferon-β and one of the anti-tumour necrosis factor-α drugs.